Multivariable and vector calculus : an introduction - Musa, Sarhan M. (Dulles, Virginia : David Pallai Mercury Learning and Information, 2015)
Rather than concentrating on technical skills, this book focuses on a deeper understanding of the subject by providing many unusual and challenging examples. The basic topics of vector geometry, differentiation and integration in several variables are explored. It also provides numerous computer illustrations and tutorials using MATLAB (R) and Maple (R).
Chapter 1: Vectors and Parametric Curves -- Chapter 2: Differentiation -- Chapter 3: Integration .
Includes index.
Keywords: CALCULUS; MULTIVARIABLE